Quality of care for ischemic stroke in China vs India: Findings from national clinical registries. (2nd October 2018) - Li, Zixiao; Pandian, Jeyaraj; Sylaja, P.N.; Wang, Yilong; Zhao, Xingquan; Liu, Liping; Wang, Chunjuan; Khurana, Dheeraj; Srivastava, M.V. Padma; Kaul, Subhash; Arora, Deepti; Schwamm, Lee H.; et al.
Abstract : Objective: To understand stroke risk factors, status of stroke care, and opportunities for improvement as China and India develop national strategies to address their disproportionate and growing burden of stroke. Methods: We compared stroke risk factors, acute management, adherence to quality performance measures, and clinical outcomes among hospitalized ischemic stroke patients using data from the Indo-US Collaborative Stroke Project (IUCSP) and China National Stroke Registry-II (CNSR-II). The IUCSP included 5 academic stroke centers from different geographic regions (n = 2, 066). For comparison, the CNSR-II dataset was restricted to 31 academic hospitals among 219 participating sites from 31 provinces (n = 1, 973). Results: Indian patients were significantly younger, had health insurance less often, and had significantly different risk factors (more often diabetes mellitus, dyslipidemia, and coronary heart disease; less often prior stroke, hypertension, atrial fibrillation, and smoking). Hospitalized Indian patients had greater stroke severity (median NIH Stroke Scale score 10 vs 4), higher rates of IV thrombolysis within 3 hours (7.5% vs 2.4%), greater in-hospital mortality (7.9% vs 1.2%), and worse outcome (3-month modified Rankin Scale score 0–2, 49.3% vs 78.1%) (all p < 0.001). The poorer clinical outcomes were attributable mainly to greater stroke severity in IUCSP patients. Chinese patients more often received antithrombotics, stroke education, and dysphagia screening during hospitalization. Conclusion: These data provide insights into the status of ischemic stroke care in academic urban centers within 2 large Asian countries. Further research is needed to determine whether these patterns are representative of care across the countries, to explain differences in observed severity, and to drive improvements.